EXPERIENCED CITY, REPRESENTED CITY: ANALYSIS OF URBAN PRACTICES IN THE NEW ALI MENDJLI CITY IN CONSTANTINE - Sandra Redjem; Ahcene Lakhel (International Journal of Innovative Technologies in Social Science, 2024)
The new Ali Mendjli town was designed primarily to meet the needs of urban expansion, and is changing as residents move in and use it on a daily basis. It is marked by a process of appropriation and reinterpretation of its urban spaces, which are strongly influenced by functional and social practices and uses. As a result, the city is an orality or a discourse made up of physical elements and symbolic representations, rituals and journeys made by social actors who in turn attribute meaning to their urban environment. The city is thus a dynamic space in which the issues of urban planning, social interaction and the appropriation of space are constantly redefined.